Penguatan Keterwakilan Perempuan Dalam Badan Permusyawaratan Desa - Kukuh Nur Priambudi (Jurist-Diction, 2022)
AbstractOne of the important institutions in the village is the BPD which is a representative institution at the village level. The element of representation in BPD is women's representation and regional representation. The active involvement of women in organizations in the village such as LKD, PKK, cooperatives, etc. shows that women play a central role in village development. Therefore, women have an urgency to get proportional representation in the Village Representative Body. The Academic Text of the Village Bill states that women's representation in the BPD must contain a 30% quota of representation. However, at the time of promulgation there was no regulation regarding the quota for women's representation in Law Number 6 Year 2014 regarding Villages, but the regulation of women's representation was actually regulated in Domestic Regulation Number 110 Year 2016 regarding the Village Consultative Body but no 30% quota for women was mentioned, but rather the representation of women in BPD is represented by one woman representative. Keywords: Village; Women's Representation; Village Consultative Body. AbstrakSalah satu lembaga penting di desa adalah BPD yang merupakan lembaga perwakilan di tingkat desa. Unsur keterwakilan dalam BPD adalah keterwakilan perempuan dan keterwakilan wilayah. Keterlibatan aktif perempuan pada organisasi-organisasi di Desa seperti LKD, PKK, koperasi, dan sebagainya menunjukkan bahwa perempuan memegang peran sentral dalam pembangunan di Desa. Oleh karena itu, perempuan memiliki urgensi untuk mendapatkan perwakilan secara proporsional dalam Badan Perwakilan Desa. Naskah Akademik RUU Desa menyebutkan bahwa keterwakilan perempuan dalam BPD harus memuat 30% kuota keterwakilan. Namun pada saat diundangkan tidak terdapat pengaturan mengenai kuota keterwakilan perempuan dalam Undang-Undang Nomor 6 Tahun 2014 tentang Desa, namun pengaturan keterwakilan perempuan justru diatur dalam Peraturan Dalam Negeri Nomor 110 Tahun 2016 tentang Badan Permusyawaratan Desa akan tetapi tidak disebutkan 30% kuota perempuan, melainkan keterwakilan perempuan dalam BPD diwakili oleh satu orang wakil perempuan.Kata Kunci: Desa; Keterwakilan Perempuan; Badan Permusyawaratan Desa.